Mitochondrial DNA 4977‐base pair common deletion in blood leukocytes and melanoma risk. (May 2016) - Shen, Jie; Wan, Jie; Huff, Chad; Fang, Shenying; Lee, Jeffrey E.; Zhao, Hua
Summary: The 4977‐base pair common deletion DmtDNA4977 is the most frequently observed mitochondrial DNA mutation in human tissues. Because mitochondrial DNA mutations are mainly caused by reactive oxygen species (ROS), and given that oxidative stress plays an important role in melanoma carcinogenesis, the investigation of DmtDNA4977 may be particularly relevant to the development of melanoma. In this study, we compared DmtDNA4977 levels in blood leukocytes from 206 melanoma patients and 219 healthy controls. Overall, melanoma cases had significantly higher levels of DmtDNA4977 than healthy controls (median: 0.60 vs 0.20, P = 0.008). The difference was evident among individuals who were older than 47 yrs, women, and had pigmentation risk factors (e.g., blond or red hair, blue eye, fair skin, light, or none tanning ability after prolonged sun exposure, and freckling in the sun as a child). The difference was also evident among those who had at least one lifetime sunburn with blistering and had no reported use of a sunlamp. Interestingly, among controls, DmtDNA4977 levels differed by phenotypic index and reported use of a sunlamp. In the risk assessment, increased levels of DmtDNA4977 were associated with a 1.23‐fold increased risk of melanoma (odds ratio (OR): 1.23, 95% confidence interval (90% CI): 1.01, 1.50). A significant dose–response relationship was observed in quartile analysis (P = 0.001). In summary, our study suggests that high levels of DmtDNA4977 in blood leukocytes are associated with increased risk of melanoma and that association is affected by both pigmentation and personal history of sun exposure.